The correlates and course of multiple health risk behaviour in adolescence - Daniel R. Hale; Russell M. Viner (BMC, 2016)
Abstract Background Health risk behaviours often co-occur in adolescence. This may be partially explained by a set of common risk and protective factors. The current study examines the association between risk behaviours throughout adolescence and identifies common risk factors for multiple risk behaviour in late adolescence. Methods We use data from the Longitudinal Study of Young People in England. We examined the association between risk behaviours at age 14 (n = 15,588), age 16 (n = 12,416) and age 19 (n = 9,548). The associations between age 19 risk behaviour and earlier risk behaviours and risk and protective factors were assessed longitudinally. Health risk behaviours included smoking, alcohol use, illicit drug use, delinquency and unsafe sexual behaviour. Results All risk behaviours were found to be associated with other risk behaviours with associations weakening through adolescence. A number of sociodemographic, interpersonal, school and family factors at age 14 predicted risk behaviour and multiple risk behaviour at 19, though predictors for heavy alcohol use often differed from other health risk behaviours. Past risk behaviour was a strong predictor of age 19 risk behaviour though many involved in only one form of risk behaviour in mid-adolescence do not progress to multiple risk behaviour. Conclusions Our findings reaffirm the links between health risk behaviours, but these diminish throughout adolescence with multiple risk behaviour usually initiated in mid-adolescence. Multiple risk behaviour is initiated in early or mid adolescence with a number of common risk factors explaining the co-occurrence of risk behaviours.